Going with the floe: Sea-ice movement affects distance and destination during Adélie penguin winter movements - D Jongsomjit; A Lescroël; AE Schmidt; S Lisovski; DG Ainley; E Hines; M Elrod; KM Dugger; G Ballard (2023)
Going with the floe: Sea-ice movement affects distance and destination during Adélie penguin winter movements